Recurrent hotspot mutations in HRAS Q61 and PI3K-AKT pathway genes as drivers of breast adenomyoepitheliomas - Felipe C. Geyer (Nature Portfolio, 2018)
Adenomyoepithelioma is a rare tumor of the breast with an unknown genetic basis. Here the authors perform a genomic analysis of adenomyoepitheliomas revealing that their repertoire of somatic mutations vary according to the estrogen receptor (ER) status, and that ER-negative tumors harbor recurrent mutations in HRAS and PI3K pathway genes.